Ο Ρόλος των βιβλιοθηκών στις κοινωνικά περιθωριοποιημένες ομάδες. - (:unkn) unknown (My University, 2021)
Στην παρούσα εργασία αναλύεται η αλληλεπίδραση που μπορεί να υπάρξει μεταξύ των ατόμων που ανήκουν σε περιθωριοποιημένες ομάδες και των βιβλιοθηκών ως δομές-κτήρια αλλά και ως υπηρεσίες που προωθούν τη φιλαναγνωσία και την αυτομόρφωση. Σκοπός της παρούσας εργασίας είναι να μελετήσει το πεδίο διάδρασης του υποκειμένου που βρίσκεται στο περιθώριο με τη βιβλιοθήκη και ως εκ τούτου τη δημόσια πρόσβαση στη πληροφορία, είτε σε επίπεδο συλλογικό είτε σε ατομικό,να ανιχνεύσει τις υπηρεσίες που προωθούνται αλλά και τους περιορισμούς που τις συνοδεύουν και να εντοπίσει τους τρόπους με τους οποίους αποτρέπεται το περιθωριοποιημένο κοινωνικά άτομο να έρθει σε επαφή και να εξοπλιστεί με τα εχέγγυα της γνώσης. Τέλος να αναδειχθούν τόσο η σημασία της περαιτέρω αξιοποίησης των βιβλιοθηκών όσο και οι τρόποι με τους οποίους αυτή μπορεί να γίνει εφικτή σε διαφορετικές κοινωνικά περιθωριοποιημένες ομάδες ανάλογα με τα χαρακτηριστικά τους.

This paper, as its title suggests, deals with the role, the value and the meaning of access to libraries by marginalized groups of people. Starting with a historical background, from antiquity to the invention of typography and to this day with the possibilities of the digital age, this work attempts to trace the importance of libraries, the democratization of information and the sharing of knowledge from the few to the many, due to the public nature of modern libraries, but also the embankments that arise and even today are encountered by socially marginalized groups. The possibility of individuals' access to libraries, the incentives given to them but also the individual initiative in combination with the collective promotion by society for the concept of literacy, knowledge and the importance of information are the main axes that are studied and they concern socially marginalized groups, such as detainees in detention centers, people with disabilities, Roma communities, people on the street and those who do not have knowledge of the Greek language. The factors that make it difficult for socially marginalized people to access libraries, which will be analyzed below, only intensify the need to strengthen this aspect and operation of public libraries, but also reinforce the argument that libraries, as buildings and as services, are one of the key pillars for implementing an inclusive policy that promotes self-education, inclusion, equality and social justice in civil society.
Keywords: βιβλιοθήκες, προσβασιμότητα, κοινωνικά περιθωριοποιημένες ομάδες, συμπερίληψη, ιστορία, ΑμεΑ, ρομά, καταστήματα κράτησης; libraries, accessibility, socially marginalized groups, inclusion, history, disabled, Roma, detention centers